Evaluating the efficacy of TeleFAMILIES: a telehealth intervention for caregivers of community-dwelling people with dementia. (14th July 2022) - Rice, Jasmen D.; Sperling, Scott A.; Brown, Daniel S.; Mittleman, Mary S.; Manning, Carol A.
Abstract: Objectives : Examine the efficacy of a telehealth-administered intervention for caregivers of persons with dementia. Method : Two hundred sixteen caregivers engaged in the FAMILIES intervention over six months, either virtually ( n  = 59) or in-person ( n  = 157). The telehealth protocol (TeleFAMILIES) was conducted online. Caregivers engaged in six sessions, including individual and family/group counseling, ad hoc counseling, and had access to support groups. Sessions included person-centered assessments of caregivers' physical, emotional, social needs, and current support networks. Primary outcome variables were change in total score between baseline and completion on the Zarit Burden Interview (ZBI), Center for Epidemiologic Studies Depression Scale-Revised (CESD-R), and the Revised Memory and Behavior Problems Checklist (RMBPC). Results : TeleFAMILIES caregivers reported significant reductions in ZBI ( p = .002) and CESD-R scores ( p < .001). RMBPC reaction scores significantly improved ( p = .02) and improved more than in-person caregivers' scores (F (3, 119) = 2.71, p = .048, partial eta 2 = .06). For those classified as having a higher risk of depression at baseline, a significantly larger portion TeleFAMILIES caregivers converted to a classification of lower depression risk at completion ( p = .02). Conclusion : Compared to the in-person group, TeleFAMILIES caregivers experienced the same, if not greater improvements in perceived burden, depressive symptomatology, and their ability to manage their reactions to behavioral symptoms of dementia. The strengths of TeleFAMILIES are the convenience of telehealth services and its mitigation of barriers to care.